Pemanfaatan Media Digital Instagram untuk Penguatan Citra Pemerintah Kabupaten Bogor - Arummaisya Rosdiana Zuhra; Hari Otang Sasmita (Unitri Press, 2026)
Instagram has become one of the strategic media in government communication because it is able to disseminate information quickly, widely, and interactively. However, its effectiveness in building a positive image of local government still requires further study, particularly regarding the role and communication strategies of public relations in managing content and engaging the community. This study aims to explain the role of the Bogor Regency Communication and Information Agency's public relations division in utilizing Instagram as a platform for strengthening government image, as well as to analyze the communication strategies applied in managing the official @kabupaten.bogor account. This research uses a descriptive qualitative method through observation, interviews, active involvement in the workflow of the public relations team, and literature study. Data were collected from the public relations work processes, including pre-production, production, and post-production of content. The results show that public relations play an important role in delivering transparent, accurate, and accessible information. The communication strategy used refers to The Circular Model of Social Media (SOME), which includes the stages of Share, Optimize, Manage, and Engage. The use of features such as stories, live streaming, polls, reposts, and comments is proven to enhance interaction and strengthen two-way communication with the public. Abstrak Instagram menjadi salah satu media strategis dalam komunikasi pemerintah karena mampu menyebarkan informasi secara cepat, luas, dan interaktif. Namun, efektivitas pemanfaatannya dalam membangun citra positif pemerintah daerah masih perlu diteliti lebih dalam, terutama terkait peran serta strategi komunikasi humas dalam mengelola konten dan membangun keterlibatan publik. Penelitian ini bertujuan untuk menjelaskan peran Humas Diskominfo Kabupaten Bogor dalam memanfaatkan Instagram sebagai sarana penguatan citra pemerintah, serta menganalisis strategi komunikasi yang diterapkan dalam pengelolaan akun resmi @kabupaten.bogor. Metode penelitian yang digunakan adalah deskriptif kualitatif melalui observasi, wawancara, keterlibatan langsung dalam alur kerja humas, serta studi pustaka. Data dikumpulkan dari tahapan kerja humas yang meliputi pra-produksi, produksi, dan pasca-produksi konten. Hasil penelitian menunjukkan bahwa humas berperan penting dalam menyampaikan informasi yang transparan, akurat, dan mudah dipahami publik. Strategi komunikasi yang digunakan mengacu pada The Circular Model of Social Media (SOME), yaitu Share, Optimize, Manage, dan Engage. Pemanfaatan fitur Instagram seperti stories, live, polling, repost, dan komentar terbukti meningkatkan interaksi serta memperkuat komunikasi dua arah antara pemerintah dan masyarakat.